Effect of Magnetic Oxidation and Surface Carbon Distribution on Friction and Wear Characteristics of 45 Steel under the DC Magnetic Field. Issue 5 (3rd September 2019) - Xie, Yulong; Sun, Chao; Zhang, Yongzhen; Shi, Hongxin; Song, Chenfei; Du, Sanming
Abstract: The sliding dry friction behaviors and wear properties of normalized 45 steel and annealed 45 steel under different magnetic field intensities were experimentally studied using a self-made HY-100 pin–disc friction and wear tester. The influence of a magnetic field on the friction and wear of 45 steel were also investigated by analyzing the microscopic friction surface and subsurface using a 3D shape analyzer and metallographic microscope. The experimental results show that the friction coefficient of the normalized 45 steel was greater than that of the annealed 45 steel under magnetic field. In addition, the results illustrate that the external magnetic field can effectively improve the wear performance of carbon steel. The wear rate of normalized 45 steel was lower than that of annealed 45 steel. The wear performance of normalized 45 steel was more significantly improved compared to annealed 45 steel with a magnetic field. Energy spectrum analysis indicated that the effect of the magnetic field on the degree of friction and oxidative wear of the normalized 45 steel was weaker than that of the annealed 45 steel, and the ratio of oxygen to iron and the oxidation area on the friction surface of the normalized 45 steel were smaller. It is believed that as an oxidation protectant, carbon reduces the oxidation wear of 45 steel. The carbon on the normalized 45 steel surface was uniformly distributed and the protective effect of friction surface was better. Therefore, the oxidation wear and oxide shedding were reduced and the wear performance was improved.